Digital Economy Creative System Using Laravel Based Responsives Web at Rumah Terang Ministries Production House - Daniel Yeri Kristiyanto; Sisilia Thya Safitri; Fadiana Fadiana (Diponegoro University, 2025)
Rumah Terang Ministries is a creative economy production house that focuses on digital multimedia such as flat design, motion, films, movies and podcast content. This production house has been running and growing in its marketing media. The production house has target development and general market than before with Christian spiritual content. This is what makes Rumah Terang Ministries turn into a more general production house and requires digital marketing. The use of the website is seen as a solution as well as a system to bridge between content creators and consumer. Object oriented programming-based websites are considered capable of handling the needs of this Laravel based digital production house. Technically, the website that was built was using the Models Views Controller (MVC) concept based on the Laravel version 9 backend framework. The database system was developed using MariaDB 10.4.24 PHP 8.1.4, frontend using CSS Bootstrap version 5.2. The system that was built has a specific purpose as a media partner for creative economy digital product capable of broadcasting, branding, delivering consumers by map, as well as media engagement between production houses and consumers. Furthermore, every ongoing project has a professional work base and has a good engagement framework. Web media can also be accessed by customers in various places to that it is easier for customers to make deals with the production house.